If it's not what You are looking for type in the equation solver your own equation and let us solve it.
10x=9(x+7)
We move all terms to the left:
10x-(9(x+7))=0
We calculate terms in parentheses: -(9(x+7)), so:We get rid of parentheses
9(x+7)
We multiply parentheses
9x+63
Back to the equation:
-(9x+63)
10x-9x-63=0
We add all the numbers together, and all the variables
x-63=0
We move all terms containing x to the left, all other terms to the right
x=63
| -27-2w=7w+36 | | -3(x-5)+6(x+2)=9 | | 5(4-x)-7(-x+2)=4-9+3 | | 10(w-2)-3(w+2)=3-4(w-1) | | 7(u+7)-10u=5(3-4u) | | 5(z-9)+2(z+6=17+3(z+2) | | 7x/8-8=7 | | 9x+11=8x+13 | | 1t-7=7t | | 45*4+56/x=5 | | 5x-9x-6=3 | | 3^2x+3^x-21=0 | | 0.8x-15=0.8(6x-8) | | 29=23+11x+2 | | 29=23+11x+2/2 | | 11x+2=23+29/2 | | 4x-2*(-2x+5)=10 | | 1=4^3x-4 | | 500.000=d(1-(1+0.06/12)^-20(12) | | 0.3n=6.39 | | (4x+35)=(7x-10) | | 5y=315 | | 3x(x-4)-7=2(x-3) | | x+33=x^2+10 | | 6x-8=4x+13= | | 100-1/3=4p-120 | | w=-2.4*20+62 | | X+2x+6x=30 | | -100t=10t-5t | | (2x-1)(x+2)=666 | | Y4+5y-3=0 | | 7x+3x+25=35 |